PRACTICUM IMPLEMENTATION ANALYSIS IN CHEMISTRY LEARNING IN HIGH SCHOOL IN BANDA ACEH - Hilda Yusmarina; Latifah Hanum; Ratu Fazlia Inda Rahmayani (Chimica Didactica Acta, 2021)
It has been conducted a research entitled "enforcement analysis of the works in chemistry studies at Banda Aceh high school." The purpose of this study is to analyse the practice of chemistry studies in all high schools in Banda Aceh. The kind of research used was descriptive research with a survey approach. This research was conducted at high school in Banda Aceh. The reasons for the selection of a research facility, based on observations of high school researchers in the city of Banda Aceh is still lack of practical activities. The population in this study are all the teachers of chemistry in Banda Aceh high school of 78 people. The sample used in this study is twenty five of chemistry teachers. The selection of samples is conducted in a random sampling way by the researchers' consideration that the sample was considered homogeneous since high school at Banda Aceh was accredited to A. Data collection techniques were carried out by a wider distribution of questionnaires. The instrument used is a questionnaire. Based on research done on the implementation of the practice in chemistry  at the high school of Banda Aceh, it could be concluded that the performance of the law in chemical study at the city high school of BandaAceh was perfectly great with an average percentage of what obtained was 88%.